2019
DOI: 10.3390/ijerph16061006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Eicosanoid Levels and Serum Levels of Metabolic and Hormonal Parameters Depending on the Presence of Metabolic Syndrome in Patients with Benign Prostatic Hyperplasia

Abstract: Background: The purpose of our investigation was to analyze the relationship between the serum levels of inflammatory mediators (HETE, HODE) and the levels of selected metabolic and hormonal parameters in patients with benign prostatic hyperplasia (BPH) with regard to concomitant metabolic syndrome (MetS). Methods: The study involved 151 men with BPH. Blood samples were taken for laboratory analysis of the serum levels of metabolic and hormonal parameters. Gas chromatography was performed using an Agilent Tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…5-oxo-ETE and 15-oxo-ETE are the metabolites of 5-HETE and 15-HETE, respectively. Grzesiak et al reported that TG was correlated with 5-HETE and 15-HETE, TC was correlated with 15-HETE in patients with both benign prostatic hyperplasia (BPH) and metabolic syndrome (MetS), and lipid mediators of inflammation, which influence the levels of biochemical parameters, may contribute to the mechanism (Grzesiak et al, 2019). Furthermore, our results indicated that PGB2, PGE2, 16-HETE, 18-HETE, 8,9-DHET, and 7-HDoHE were correlated with the function of the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…5-oxo-ETE and 15-oxo-ETE are the metabolites of 5-HETE and 15-HETE, respectively. Grzesiak et al reported that TG was correlated with 5-HETE and 15-HETE, TC was correlated with 15-HETE in patients with both benign prostatic hyperplasia (BPH) and metabolic syndrome (MetS), and lipid mediators of inflammation, which influence the levels of biochemical parameters, may contribute to the mechanism (Grzesiak et al, 2019). Furthermore, our results indicated that PGB2, PGE2, 16-HETE, 18-HETE, 8,9-DHET, and 7-HDoHE were correlated with the function of the thyroid.…”
Section: Discussionmentioning
confidence: 99%